Assessment of Intravitreal Injection Training among U.S.-Based Ophthalmology Residents - Liechty, Jacob J.; Wilkinson, Michael J.; Bowie, Esther M. (Journal of Academic Ophthalmology, 2019)
Purpose To describe the intravitreal injection training of ophthalmology residents in the United States in 2018.Design Cross-sectional survey.Methods An anonymous, 29-question, internet-based survey was emailed to 119 ophthalmology residency program directors with the instructions to forward the survey to their ophthalmology residents.Results A total of 117 ophthalmology residents (7.89%) responded to the survey. The majority of residents stated that their intravitreal injection training began during their first year of ophthalmology training, PGY 2 year, (92.3%). The majority of residents performed at least 25 injections per year (78.6%). All residents use antiseptic on the conjunctiva prior to the injection, 94% use a lid speculum, and 84.6% avoided talking in the procedure room. Most injections are performed with gloves (83.8%). A minority of residents stated that they are trained to use povidone-iodine on the eyelids prior to performing an injection (45.3%). Only 6.0% of residents claimed to use postinjection antibiotic drops. Performance of bilateral, simultaneous intravitreal injections was split with nearly half of residents not being trained in this method (47.9%).Conclusion Ophthalmology residents from across the country experience a variety of different injection protocols when being trained on how to perform intravitreal injections. Conjunctival antisepsis has reached a clear consensus while topics such as simultaneous, bilateral injections and eyelid antisepsis are still uncertain among the resident community.
Keywords: resident; training; intravitreal; retina